Voluntary Nonprofit Enterprise Management - Mason, David. author. aut Link
XIII, 192 p. 3 illus.
Keywords: My values, attitudes, and behaviors, like those of most Americans, have been profoundly influenced by not-for-profit enterprises. My parents were students in one when they met. I was born in one. I learned about God in one, my ABCs in another, how to make a fire and tie knots in another, how to play ball and be part of a team in another, and I met my first girlfriend in another. I prepared for my career at a not-for-profit university, met my wife at a not-for-profit church, went on to several not-for-profit graduate schools, joined numerous not-for-profit profes sional and special interest groups, brought two newly born sons horne from not-for-profit hospitals. I read magazines published by several of them, sail Cj. nd hunt with their members, and when I vote I consider a variety of their admonitions. Voluntary not-for-profit enterprises have been molding and shaping me as long as I have been alive, and they will even be represented at my funeral. Therefore, it seems only fair that I should help to shape some of them. I have been at that task for some time now-Ieading seminars, consulting, writing, and serving on boards and committees. This book is an outgrowth of what I have learned through formal study, observation and analysis, and personal experience in more than half the states of the union and many foreign nations.